Credit Union Policies and Performances in Latin America - Glenn Westley; Sherrill Shaffer (Inter-American Development Bank, Office of the Chief Economist, 1997)
This paper presents a conceptual framework for explaining credit union (CU) loan delinquency and profitability in developing countries. It also offers an empirical estimation for a unique sample of Latin American CUs.
Keywords: 330; Genossenschaftsbank; Bürgschaftsbank; Rentabilität; Gewinn; Schätzung; Lateinamerika